Editors and Guidelines of the EDUCARE Journal, Issue of August 2017 - Journal, Editor EDUCARE (EDUCARE, 2017)
EDUCARE: International Journal for Educational Studies.Â This journal, with ISSN 1979-7877, was firstly published on August 17, 2008, in the context to commemorate the anniversary of Indonesian Independence Day. Since issues of February 2009 to February 2016, the EDUCARE journal was organized and managed by the Lecturers of FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto) in Central Java; and published by Minda Masagi Press, as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The EDUCARE journal is published twice a year, i.e. every August and February.Bandung, Indonesia: August 30, 2017.Sri Redjeki Rosdianti, M.M.Pd.Director of Minda Masagi Press in Bandung, West Java, Indonesia.